Sprinkle Your Investment Portfolio with Water! - Jin, Y.; Roca, E.; Li, B.; Wong, V.; Cheung, Adrian (Inderscience Publishers, 2015)
This paper investigates the profitability of water-related investments and their diversification benefits in a portfolio context. Motivated by the need to understand whether or not water indices and water funds are desirable vehicles for investment, we analyse the performance of a major water index independently, as well as within portfolios. Our results indicate that the water asset class outperforms traditional asset classes, and has the capacity to produce diversification effects in portfolios primarily comprised of listed equity and bond assets. In addition, our study suggests that the diversification benefits of the water asset class are likely to be a result of its superior performance over the stock benchmark, rather than its low correlation with traditional asset classes. Our study provides a valuable contribution to the small, yet growing body of literature on water investments.